Emissões de CO2 em solos do Cariri paraibano com diferentes usos e cobertura da terra - Lourenço, Elloise Rackel Costa (2022)
Soil carbon dioxide (CO2) emissions, also referred to as soil respiration (SR), is an important component of the global carbon balance. RS comes from microbial activity, root system respiration and soil organic matter (SOM) decomposition. With the modification of ecosystems, particularly through deforestation and agricultural activities, the constant use of terrestrial carbon stock can accelerate the process of changes in climate dynamics, causing an increase in temperature. Studies focused on this theme are scarce and important for understanding global changes, especially when it comes to the efflux of CO2 from the soil in areas of the Caatinga biome. In this scenario, the study aimed to evaluate the soil CO2 efflux in areas with different land cover (agricultural areas, degraded areas and preserved areas) in the Caatinga biome. The study was conducted on a property located in the Cariri Environmental Protection Area (APA), at Fazenda Salambaia, located in the immediate geographic region of Campina Grande and in the micro-regions of Cariri Paraibano and Campina Grande, State of Paraíba, Brazil. The activities of this research involved mapping land use and quantifying CO2 emissions, biomass, rainfall, soil moisture and temperature in areas under different land uses and land cover, using in situ measurements and sensing techniques. remote. CO2 emission data were collected by the infrared absorption gas analyzer method (IRGA), soil moisture and temperature, in the dry and rainy seasons, during the years 2017 and 2018, at ten points with different characteristics. The largest efflux of CO2 occurred in areas where there is presence of preserved vegetation, lower temperatures and in the rainy season. There was a correlation with types of land use, accumulated precipitation, soil components and seasonal variations, but no correlations were found with temperature and soil moisture. The results also identified the presence of CO2 influx in areas with degraded vegetation, characterizing a situation of desertification in them.